2014, Nr. 15A, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Challenges of auditing and internal controlIndrė Pečiulytė, Juozas Ruževičius, Quality audit typology and methodology, 8Darius Vaicekauskas, Analysis and evaluation of Lithuanian public interest companies audit market, 26Rasa Kanapickienė, Živilė Grundienė, Actions to detect fraud in financial statements, 37Aleksandra Pečiūrienė, Analytical procedures in volatile business entities audit context, 47Lukas Giriūnas, Jonas Mackevičius, The expression of the elements of the internal control system graphical representation, 62Gintarė Giriūnienė, The research of professional ethics of tax auditor seeking the trust in tax, 73Živilė Simonaitytė, Analysis of internal control models, 82Problems of economics and financeMilda Švedienė, Astrida Slavickienė, The impact of notional defined contribution system (NDC) from the point of view of individual, 96Artūras Jurgelevičius, Social economic risk analysis of Lithuania in the context of European Union countries, 106Deimena Kiyak, Laura Paulionienė, Activity evaluation of Lithuania credit unions, 118Jūratė Každailienė, Dalia Daujotaitė, Assessment of trade credit risk in business companies, 133Emilija Narbuntaitė, Agnė Ramanauskaitė, The assessment of shadow economy in Lithuania, 149Jovita Kalantaitė, Rasa Subačienė, Impact  of Lithuanian tax reform to companies results, 162Jonas Martinavičius, Preparation of trade specialists at VU faculty of economics and their correspondence to market needs, 178Lukas Giriūnas, Jonas Mackevičius, Analysis of Professor Vladas Jurgutis thoughts on the money and its development in the Lithuanian scientific literature, 191
Keywords: none